(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The article discusses case and exercise systems, the concept of case, guidelines for creating exercises and tasks, various types of exercises and training for assessing, comparing, and creating different activities.